PARTISIPASI DAN KETERWAKILAN PEREMPUAN Sebagai Upaya Demokratisasi di Indonesia - Sofiyah, Siti Lailatus (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2007)
Participation is people's participation in planning, implementing, and evaluating a developing program. ItÂ isÂ an access or people's control to the goverment and the development which influence the citizens of a country. It is also part of human right (whether men or women). However, Women's participation in political arena, especially in political party still shows insignificant feature for several factors such as family responsibility of caring children. Therefore, in the context of democratization process, the quantity of participation in politics (political party and parliamentary) must consider women's participation level as they are also part of the country and the democratization process itself.